Antiwomen But Proquota: Disaggregating Sexism and Support for Gender Quota Policies. Issue 2 (17th October 2020) - Beauregard, Katrine; Sheppard, Jill
Abstract : Previous research on support for gender quotas focuses on attitudes toward gender equality and government intervention as explanations. We argue the role of attitudes toward women in understanding support for policies aiming to increase the presence of women in politics is ambivalent—both hostile and benevolent forms of sexism contribute in understanding support, albeit in different ways. Using original data from a survey conducted on a probability‐based sample of Australian respondents, our findings demonstrate that hostile sexists are more likely to oppose increasing of women's presence in politics through the adoption of gender quotas. Benevolent sexists, on the other hand, are more likely to support these policies than respondents exhibiting low levels of benevolent sexism. We argue this is because benevolent sexism holds that women are pure and need protection; they do not have what it takes to succeed in politics without the assistance of quotas. Finally, we show that while women are more likely to support quotas, ambivalent sexism has the same relationship with support among both women and men. These findings suggest that aggregate levels of public support for gender quotas do not necessarily represent greater acceptance of gender equality generally.